PENGEMBANGAN MODEL PEMBELAJARAN CABANG OLAHRAGA ATLETIK LARI 100 METER MELALUI MEDIA VIDEO SISWA KELAS VII SMP NEGERI 2 REJANG LEBONG - Taqwin, Ahsani (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2021)
This research is a type of research and development with a Research and Development (R&D) form according to Sugiono. This development form goes through 10 stages of procedures adapted from Sugiono, namely the design stage, potential and problems as well as information data collection, product design, design validation, design revision, small group trials, design revisions, large group trials, product revisions after group trials. large, mass production. The subjects of the small-scale research were 15 students of class VII Junior High School 2 Rejang Lebong, and on a large scale 3 grade VII students of Junior High School 2 Rejang Lebong totaled 30 people. Data obtained from a questionnaire. The results of the small group trial got an average score of 80% in the